Use of Erbium Laser in the Treatment of a Patient with Acute Purulent Periostitis and a Resistant Form of Primary Immune Thrombocytopenia - Elena Larionova; Svetlana Tarasenko; Elena Morozova; Ekaterina Diachkova (Hindawi Limited, 2019)
In our article, we described a clinical case of a patient with an acute periostitis of the maxilla with a comorbidity (primary immune thrombocytopenia, resistant form) who was treated using laser technology allowing us to provide good results: an intensive regeneration process and a decreased risk of developing infection complications and unpleasant signs for the patient, such as postoperative edema and intraoperative and postoperative pain syndrome.